Improvement of student’s argumentation skill through problem-based learning in the concept of nerveous and endocrine system disorders - Lutfiani, Resti; Hamdiyati, Yanti; Suhaeni, Lilis (Assimilation: Indonesian Journal of Biology Education, 2024)
21st-century education directs learners to develop the skills of argumentation. Argumentation skills are the intellectual abilities involved in solving problems, making judgments and decisions, and formulating ideas and beliefs. The purpose of this research was to improve students' argumentation skills through the implementation of the Problem-based learning model in the concept of nervous and endocrine system disorders. This study was Collaborative Classroom Action Research with two learning cycles in the concept of Nervous and Endocrine System disorders. This study reveals students' argumentation skills adapted from Dawson Venville (2009). The results of this research revealed that the level of students' argumentation skills in cycle I was only up to levels 1 and 2. As much as 59% of students were at level 2 argumentation skills and 41% of students were at level 1 argumentation skills. In cycle II, there are students with level 3 argumentation skills. The rest scattered on levels 1 (3% of students) and 2 (35% of students) argumentation skills. Through this research, we found that students' argumentation skills increased from cycle I to cycle II.